Differences in the Role of Psychological Well-Being and Subjective Well-Being in Predicting Work Engagement - Reny Yuniasanti; Fonny Dameaty Hutagalung; Alimatus Sahrah; Nina Fitriana (Universitas Muhammadiyah Surakarta, 2024)
Employees with high Work Engagement (WE) are believed to be more reliable in achieving organizational goals. This research aims to determine the differences in the role of well-being with the concepts of hedonic and eudemonic in predicting WE. The subjects of this research consisted of 327 people, who were analyzed in 3 stages, namely 110 people who were analyzed in stage-1, 217 people who were analyzed in stage-2, and all research subjects were analyzed in stage-3. All data for this research were collected using the WE scale, PWB scale, SWFL scale, and PANAS, which have a Chronbach alpha reliability coefficient of .773 respectively; .831; .627; 747; 744. In stage-1 research analysis, SWB and PWB show more of just one component, whereas in stage-2 and stage-3 research analysis, they are more likely to be seen as two different factors in predicting WE. The results of the stepwise model multiple regression statistical technique analysis concluded that the regression coefficient on the influence of SWB and PWB on WE from the three analyses stated that PWB was stronger than SWB in predicting WE. Thus, it can be interpreted that to predict WE the Well-Being concept with the eudemonic concept is greater than using well-being with the hedonic concept.